Depression in patients with type 2 diabetes attending at Chao Phya Abhaibhubejhr Hospital - Nueangjaknak, Amporn; Suppapitiporn, Siriluck (Chulalongkorn Medical Journal, 2023)
Background: Diabetes mellitus (DM) is one of the most common public health problems worldwide. It is a chronic, debilitating disease that needs lifelong care for both physical and psychological aspects. Previous studies on depression in diabetic patients are scant in Thailand. Objective: To determine the prevalence of depression and its associated factors in patients with type 2 diabetes at Chao Phya Abhaibhubejhr Hospital, Prachinburi Province. Methods: A cross-sectional descriptive study was conducted among patients with type 2 diabetes at the Outpatient Clinic of Chao Phya Abhaibhubejhr Hospital, Prachinburi Province, Thailand from August to December 2017. The instruments were demographic and clinical characteristics questionnaires, the Thai Hospital Anxiety and Depression Scale (Thai HADS), Health Perception Questionnaire, and family status and functioning assessment scale. The statistics used to analyze data were frequencies, percentages, mean and standard deviation, Chi-square test, Fisher exact test, Pearson product-moment correlation coefficient and logistic regression. Results: Of the total 355 participants, the mean age was 55.7 years, 60 % had been diagnosed type 2 diabetes for more than 5 years; 25 % had used traditional herbs. The prevalence of depression in patients with type 2 diabetes was 20.8 %. Depression was significantly related to the age group above 50 years old, unemployment, licorice herb use and lower family functioning. Conclusion: One-fifth of the patients with type 2 diabetes were found to have depression. The results of this study will be beneficial for recognizing depression and providing appropriate care for patients with type 2 diabetes.